Prevalence of viral photosynthesis genes along a freshwater to saltwater transect in Southeast USA. Issue 5 (16th July 2019) - Ruiz‐Perez, Carlos A.; Tsementzi, Despina; Hatt, Janet K.; Sullivan, Matthew B.; Konstantinidis, Konstantinos T.
Summary: Bacteriophages encode host‐acquired functional genes known as auxiliary metabolic genes (AMGs). Photosynthesis AMGs are commonly found in marine cyanobacteria‐infecting Myoviridae and Podoviridae cyanophages, but their ecology remains understudied in freshwater environments. To advance knowledge of this issue, we analysed viral metagenomes collected in the summertime for four years from five lakes and two estuarine locations interconnected by the Chattahoochee River, Southeast USA. Sequences representing ten different AMGs were recovered and found to be prevalent in all sites. Most freshwater AMGs were 10‐fold less abundant than estuarine and marine AMGs and were encoded by novel Myoviridae and Podoviridae cyanophage genera. Notably, several of the corresponding viral genomes showed endemism to a specific province along the river. This translated into psbA gene phylogenetic clustering patterns that matched a marine vs. freshwater origin indicating that psbA may serve as a robust classification and source‐tracking biomarker. Genomes classified in a novel viral lineage represented by isolate S‐EIVl contained psbA, which is unprecedented for this lineage. Collectively, our findings indicated that the acquisition of photosynthesis AMGs is a widespread strategy used by cyanophages in aquatic ecosystems, and further indicated the existence of viral provinces in which certain viral species and/or genotypes are locally abundant.